The Art of Performance in the Late Xix Century (1860-1917) - Olimjon, Tursunov (International Journal on Orange Technologies, 2022)
This article describes the history of the performing arts, the practice of folk classical music of the XIX century, traditions and the work of Central Asian ethnographic and folklorists of the 70-80s of the XIX century.